Evaluation of Some Long Bean Lines Using Early and Late Produced Seeds in Two Soil Types - Yap, Thoo Chai; Cheok, K. T. (1978)
Early and late produced seeds of some F9 lines and exotic cultivars of long beans were evaluated on clayey loam and alluvial soil in the University Farm at Serdang. The results showed that pod yield and pod length were not significantly different for seeds produced early or late. Among the genotypes studied, pod yield was more unstable than pod length. However, some lines and Taiwan Stripe Seed performed better than the ,local commercial variety, Local Long-l in both soil types.